ChemInform Abstract: Alkaline‐Earth‐Catalyzed sp3 C—H Functionalization of Methyl Azaarenes and Its Use in a One‐Pot Four‐Component Synthesis of Azaarenyl Benzylpyrazolones. Issue 33 (27th July 2016) - Yaragorla, Srinivasarao; Dada, Ravikrishna; Singh, Garima
Abstract: For the first time, calcium triflate is used to catalyze a 4‐component reaction between aldehydes, 2‐methylquinolines, ethyl acetoacetate, and arylhydrazines to give 1‐aryl‐3‐methyl‐4‐ [2‐(quinolin‐2‐yl)‐1‐aryl/alkyl‐ethyl]‐2H‐pyrazol‐5‐ones.